Standards for the development and methodology of the 2019 International Working Group on the Diabetic Foot guidelines. (9th January 2020) - Bus, Sicco A.; Van Netten, Jaap J.; Hinchliffe, Robert J.; Apelqvist, Jan; Lipsky, Benjamin A.; Schaper, Nicolaas C.; ,
Abstract: Diabetic foot disease is a source of major patient suffering and societal costs. Investing in evidence‐based international guidelines on diabetic foot disease is likely among the most cost‐effective forms of health care expenditure, provided the guidelines are outcome focused, evidence based, and properly implemented. The International Working Group on the Diabetic Foot (IWGDF) has published and updated international guidelines since 1999. The 2019 updates are based on formulating relevant clinical questions and outcomes, rigorous systematic reviews of the literature, and recommendations that are specific, and unambiguous along with their transparent rationale, all using the Grading of Recommendations Assessment Development and Evaluation (GRADE) framework. We herein describe the development of the 2019 IWGDF guidelines on the prevention and management of diabetic foot disease, which consists of six chapters, each prepared by a separate working group of international experts. These documents provide guidelines related to diabetic foot disease on prevention; offloading; peripheral artery disease; infection; wound healing interventions; and classification of diabetic foot ulcers. Based on these six chapters, the IWGDF Editorial Board also produced a set of practical guidelines. Each guideline underwent extensive review by the members of the IWGDF Editorial Board as well as independent international experts in each field. We believe that adoption and implementation of the 2019 IWGDF guidelines by health care providers, public health agencies, and policymakers will result in improved prevention and management of diabetic foot disease and a subsequent worldwide reduction in the patient and societal burden this disease causes.